Corporate - community partnership towards sustainability the case of the community-based organizations in Mauban, Quezon, Philippines - Geges, Dhino B.; Rivera, Rowena D.; Albor, Rufo Gil Z.; Torio, Dian A. (2014)
This case study described the corporate-community initiatives between two community-based organizations in Mauban, Quezon, Philippines. It specifically aimed to describe the socio-economic attributes of the members of the organizations; discuss the existing Corporate Social Responsibility (CSR) programs of Quezon Power Ltd; determine existing strategies engagement; and propose recommendations to further enhance the partnership strategies Data were gathered using qualitative methods. Results showed that there were opportunities and mechanisms to further improve and sustain CSR efforts of the company. Market linkage, network building and continuous capacity building through a collaborative governance approach were found to be salient ingredients in assuring sustainability. Matching of the organizational skills, capabilities and resources, on the other hand, were seen as critical activities. The value chain strategy was also perceived to be helpful in anchoring the micro-enterprise to the needs of the market. Essentially, establishing market-driven business activities and provision of business advisory services to the organizations are considered to be vital.
Keywords: Social responsibility of business; Sustainability